2017
DOI: 10.7717/peerj.2902
|View full text |Cite
|
Sign up to set email alerts
|

Accelerometer-measured physical activity is not associated with two-year weight change in African-origin adults from five diverse populations

Abstract: BackgroundIncreasing population-levels of physical activity (PA) is a controversial strategy for managing the obesity epidemic, given the conflicting evidence for weight loss from PA alone per se. We measured PA and weight change in a three-year prospective cohort study in young adults from five countries (Ghana, South Africa, Jamaica, Seychelles and USA).MethodsA total of 1,944 men and women had baseline data, and at least 1 follow-up examination including measures of anthropometry (weight/BMI), and objective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 41 publications
1
27
0
Order By: Relevance
“…Most studies that examined body mass reported no association , except for the work by Dugas et al . , who found baseline sedentary time to be associated with body mass of Ghanaian male and female participants, positively and negatively, respectively. The same authors reported no associations for participants from South Africa, Jamaica, Seychelles and the USA.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Most studies that examined body mass reported no association , except for the work by Dugas et al . , who found baseline sedentary time to be associated with body mass of Ghanaian male and female participants, positively and negatively, respectively. The same authors reported no associations for participants from South Africa, Jamaica, Seychelles and the USA.…”
Section: Resultsmentioning
confidence: 99%
“…Of the prospective studies identified, two used heart rate FLEX to measure sedentary time , with the remaining studies employing accelerometry . Follow‐up periods ranged from 2 to 5.8 years, with sample sizes ranging from 376 to 2,027 participants.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Offering indirect support for the preceding contention are the results of a 3‐year prospective study of the correlation between physical activity (quantified by accelerometry) and weight change, in nearly 2000 men and women of African origin, aged 24‐45 years, resident in different locales in five different countries: rural Ghana, urban Jamaica, urban South Africa, the Seychelles and metropolitan USA . Multiple regression techniques failed to reveal correlations between level of activity and weight change by participants in any country.…”
Section: Enthalpy Storagementioning
confidence: 99%